Effect of Actual Gas Turbine Operating Conditions on Mist/Steam Cooling Performance in a Ribbed Passage - Jianying Gong; Tieyu Gao; Junxiong Zeng; Jianqiang Hou; Zhen Li (Energies, 2019)
This study numerically examines the effect of actual gas turbine operating conditions on heat transfer characteristics in a ribbed passage with mist/steam cooling. A 60° ribbed passage with aspect ratio of 1/1 was investigated at Reynolds number of 300,000, and steam cooling was used to provide a contrast. Three main factors were considered: coolant temperature, operating pressure, and wall heat flux density. The heat transfer enhancement mechanism of mist/steam cooling was explored, and the results showed that the heat transfer performance of mist/steam cooling was superior to steam cooling. When the coolant temperature varied from 300 to 500 °C, the average Nusselt number of mist/steam cooling decreased by 26.6%, and the heat transfer enhancement ratio dropped from 15% to 10%. As operating pressure increased, the heat transfer performance factor of mist/steam firstly increased and then decreased. At an operating pressure of 1.5 MPa, the heat transfer achieved its optimal performance, and the heat transfer enhancement ratio achieved its maximum value of 15.9%. Larger wall heat flux density provided less heat transfer enhancement. When the heat flux density increased from 100,000 to 300,000 W·m−2, the average Nusselt number of mist/steam cooling decreased by 13.8%, while the heat transfer enhancement ratio decreased from 25.3% to 12.6%.